Identificação de bens edificados considerados patrimônio cultural: o caso do município de Santa Rosa. - Preissler, Camila (2010)
Among the most diverse categories of historical heritage, the edification is the one that is most present in a daily life of a community,it is an important way of cultural valorization through the generations. The preservation of a historic building in a contemporary city, for example, it implies not only the diversification of the urban landscape, but still in the maintenance of memory and the place identity. The appreciation of architectural historic heritage and the importance of its registration and preservation is an issue widely discussed. Therefore, very little is known about the architectural heritage of cities from recent settlement. The patrimonial properties are responsible for historical continuity of a community that is recognized as it is, and embodies their ideals and values, transcending generations. The use of material from the past is the essence of culture which transforms the cultural material in heritage. This work searches for the knowledge of the built properties of Santa Rosa City recognized as a cultural value. However, although there is their recognition, the lack of registration the historical knowledge and the consequent lack of disclosure of the importance of these models can lead to the disappearance of important urban icons. This work intends to collaborate in building of knowledge and serve as a warning about the necessity of studies, registrations and preservation actions turned to these architecture, through the realization of an inventory, in order to give the first steps in knowledge of Santa Rosa architecture.